An Exploratory Study of the Subject Ontogeny of Eugenics in the New Classification Scheme for Chinese Libraries and the Nippon Decimal Classification - (:unkn) unknown (My University, 2016)
This study explores the subject ontogeny of “eugenics” by documenting the class numbers for “eugenics” in all thirteen editions of the New Classification Scheme for Chinese Libraries (CCL), and all fourteen editions of the Nippon Decimal Classification (NDC). The CCL and the NDC are the major classification schemes used in Taiwan and Japan respectively. We observe the relative stability and concentration of class numbers assigned to “eugenics” in the CCL and the NDC comparing to DDC (Tennis 2012), and the semantic changes of class numbers over time. Using two union catalogs, Taiwan’s National Bibliographic Information Network (NBINet) and Japan’s National Diet Library (NDL) Search, we retrieve bibliographic records with “eugenics” (優生學 and 優生学) as subject heading. We compare the class numbers extracted from the bibliographic records and the numbers assigned in the schemes of corresponding editions. It shows the difference between the theoretical frameworks of the schemes and the catalogers’ applications. This study highlights the temporal aspect of classification schemes and how it may influence the organization and retrieval of information. It also sheds light on some limitations of current catalogs.
Keywords: classification; subject ontogeny; eugenics; New Classification Scheme for Chinese Libraries; Nippon Decimal Classification